Evaluation of Concrete with Glass and Coconut Shell in Place of Coarse Aggregate and Partially Replaced Cement (International Journal of Innovative Research in Computer Science & Technology, 2022)
Supplies for building are getting more  expensive every day. The two essential components of the  concrete are pozzolanic material and crushed rock. These  days, a lot of scientists are investigating building materials  that could both raise and lower construction prices. It has  been shown that using some industrial leftovers and  agricultural residues as construction materials, particularly in  underdeveloped countries, provide a number of real  advantages. It was discovered that there is a lot of potential  for using coconut shells to replace part of the aggregate used  in concrete. The current work consists solely of a compilation  of data related to GFRGC and earlier studies conducted by  other academics. Millions of tonnes of glass waste are  created annually.
Keywords: Glass; coconut shell; cement; aggregate